Design, synthesis, characterization, and catalytic evaluation of unsymmetric Schiff-Base calixpyrrole transition metal complexes for hydrogen evolution - Manamalage, Sachithra Somachandra (My University, 2025)
Recently, considerable advancements have been achieved in developing new molecular electrocatalysts for the production of hydrogen, such as understanding their mechanisms, factors that affect the catalytic reaction, etc. Hydrogen presents itself as a potential fuel substitute due to being a renewable energy source with zero carbon emissions, having a maximum gravimetric energy density to replace petroleum and other petroleum products. This work demonstrates the successful design, formulation, and electrochemical H₂ evaluation of a novel mono- and bimetallic Schiff-base complexes bearing unsymmetric ligands derived from a calixpyrrole framework, developed as electrocatalysts for the hydrogen evolution reaction (HER). The introduction of chemically distinct coordination binding pockets, such as salen or imidazole (termed salixpyrrole and imixpyrrole, respectively), has enabled a straightforward pathway to coordinate various transition metals into the secondary coordination sphere, leading to the construction of tunable metal complexes with enhanced catalytic properties. Both monometallic (2) and bimetallic (3) salixpyrrole complexes were found to be catalytically active in the presence of p-toluenesulfonic acid (pTSA). Mechanistic investigations indicated that 2 follows a second-order dependence on acid and first-order dependence on catalyst, whereas 3 operates via a distinct pathway. The bimetallic species exhibits exceptional catalytic performance with a TOF of 4640 s⁻¹ and significantly lower overpotential of 0.39 V, emphasizing the benefit of incorporating a second metal center into the catalyst framework. The imixpyrrole system (4), on the other hand, was developed by including an imidazole pendant group into the ligand scaffold and shown to be catalytically active for HER in the presence of various acids. Three different acid sources (anilinium.BF₄, imidazolium.BF₄, triethylammonium.BF₄) with varying pKa were selected, and HER activity was systematically evaluated in THF. Complex 4 displayed PCET behavior with a KIE value of 6.45 in the presence of weak acid and a more classical pathway (KIE =1.06) with stronger acid anilinium. The highest TOF of 33040 s⁻¹ with a lower overpotential value of 0.53 V and a faradaic efficiency of 99.3% was achieved with anilinium. Although complex 4 behaves homogeneously in the presence of both anilinium and triethylammonium acid, it displayed heterogeneous behavior with imidazolium, demonstrating the profound impact of proton source on catalytic efficiency and mechanism. A stepwise metalation strategy to synthesize heterobimetallic Schiff-base complexes was investigated next. A successful incorporation of redox-inactive Zn (II) and redox-active Cu(I) ions into the secondary coordination sphere of the imixpyrrole system resulted in two diamagnetic heterobimetallic complexes (5 and 6). The electrochemical features provide insight into metal-metal synergism, pointing to enhanced HER potential. Collectively, this work provides a new blueprint for the rational design of electronically tunable, unsymmetric Schiff-base complexes capable of efficient proton reduction. It highlights the essential roles of ligand asymmetry, proton source, and multimetallic cooperativity in governing catalytic performance, laying the foundation for the future development of next generation HER catalysts.
Keywords: Salixpyrrole; Imixpyrrole; Secoendary coordination sphere; Molecular catalysts; Hydrogen evolution reaction (HER)